Incorporating strategic management into public health emergency preparedness - Langabeer II, PhD, James R.; DelliFraine, PhD, Jami L. (Journal of Emergency Management, 2011)
Although federal funding for public health emergency preparedness has approached $10 billion since September 11, 2001, there has been little research on the value of this investment relative to competing priorities or whether these funds achieved desired goals. Although some have argued that this dearth of research is due to a lack of definition for preparedness, the authors contend that the problems result from lack of goal specificity and absence of a guiding strategy. This results in minimal cooperation between agencies and low levels of measured preparedness outcomes. By using insights from the discipline of strategic management, the authors provide guidance to the field in development of government policies for developing a comprehensive integrated preparedness strategy.